Terrorists and Special Status: The British Experience in Northern Ireland - Spillane, Jay M. (1986)
The political and social fragmentation of Northern Ireland is well known, and the violent tactics employed by some members of the warring communities are infamous. This Note examines the conflict between Britain's treatment for politically motivated criminals in Northern Ireland and the human rights guarantees provided in various international conventions. The author concludes that politically motivated terrorists are now treated differently from other criminals and, accordingly, should be accorded the status of special prisoners, with corresponding human rights protections